Information for oral and maxillofacial patients: can it be improved?. Issue 5 (June 2019) - Parvez, H.; Noorani, M.S.; Pandis, N.; Cobourne, M.T.; Seehra, J.
Abstract: The aim and objective of this study was to evaluate the quality and readability of leaflet and online Oral and Maxillofacial Surgery patient information leaflets (PILs). The quality, readability and grade level of each PIL was assessed using the DISCERN, Flesch Reading Ease and Flesh-Kincaid Grade Level instruments respectively. In total, 140 patient information leaflets were assessed. For both leaflet and online PILs, many items of the DISCERN instrument were deemed of low quality and poorly reported. The median overall quality score was 30.2. Variation in the quality and readability scores between leaflet and online PILs and those produced by various societies was evident. Overall, PILs were deemed to be of moderate quality. Online PILs were of lower quality, more difficult to read and aimed at a higher reading age level.